Glant, Remember Hungary 1956 - Essays On The Hungarian Revolution And War On Independance In American Memory - Joyce, Davis (Teaching History: A Journal of Methods, 2008)
Howard Zinn taught me long ago that objectivity is a myth, neither possible nor desirable, and that the best we can do in writing history is to be honest and open and up front about our biases and then proceed to write the best history we can. Assuming the same principle applies to book reviewing, I should note that Tibor Giant is my friend. We were colleagues for two years, 1994-96, at Kossuth University, in Debrecen, Hungary. I was the Soros Professor of American Studies; Giant and I coauthored a textbook during that time, and we have continued our relationship over the years. He is now Chair of the North American Department of the Institute of English and American Studies of the university, now known as the University of Debrecen.